An assistive tool in determining problematic internet use: validity and reliability of the “online cognition scale” in a sample of university students - Keser Özcan, Neslihan; Buzlu, Sevim (Journal of Dependence, 2005)
Objective: This study attempts to examine the validity and reliability of the Online Cognition Scale-OCS, an assistive tool developed by Davis in 2002 for determining the problematic Internet use, in a sample of university students. Method: The research was planned according to the methodological research method. 148 university students who used the Internet at least for 2 hours a week participated in the research on a voluntary basis. 73% per cent of students (n=108) were female, 27% (n=40) were male, the average age of the group was 21.01 (SD=1.563). In the research, in addition to the Online Cognition Scale-OCS, Demographical Information Form, UCLA Loneliness Scale, Beck Depression Scale and Multi-Dimensionally Perceived Social Support Scale were used as tools for collecting data. Result: For the test-re-test reliability of the scale, the Pearson correlation ratio detected for the total scale points obtained from both applications was .90, the Pearson correlation ratio detected for the social comfort sub-groups obtained from the two applications was .87, .76 for the loneliness / depression group points, .89 for the diminished impulse control sub-group points and .85 for the distraction sub-group points (p<0.001). The co-efficient of internal consistency detected for the reliability of OCS was α=.91, the total item reliability co-efficients ranged between .17-.66 As for the values in the relation between the variant of each item and the sub-group variant, they ranged between .40 and .73. In the validity test actualized with similar scales, a positive correlation was found between OSC and depression as well as loneliness and a negative one was found with the perceived social support, it was observed that the structure of the determined factor was in good harmony with the original scale. Discussion: The level of validity reliability of OCS indicates that it is an appropriate assistive tool in determining the problematic Internet use.